Polyphenolic profile of fresh chokeberry and chokeberry products - Tolić, Mandica-Tamara (Array, 2019)
Chokeberry (Aronia melanocarpa) fruits and its products are one of the richest sources of pholyphenols which may play important role in human health as for example in regulation of blood pressure levels, reducing concentrations of triglycerides, low density and total cholesterol. The objective of this study was to identify and quantify the content of pholyphenols, specifficaly phenolic acids (gallic, caffeic, p-coumaric, ellagic, chlorogenic) and flavonols (quercetin and kaempferol) using high performance liquid chromatography (HPLC) in two varieties of fresh chokeberry fruit (type Nero and Viking) and in different types of chokeberry products available from Croatian market: eleven samples of juices, three samples of powders, two samples of both capsules and dried berries and four samples of teas. The results showed that there is a difference in amount of examined polyphenols between different product categories, and significant difference was also observed within the same product group (p≤0.05). In all analysed samples the highest phenolic acid quantified was p-coumaric acid, and gallic acid was the lowest one. Berry juices from fresh chokeberry fruits had higher amount of p-coumaric acid (284.55±6.34 mgL-1) compared to commercially available juices (195.48±3.05 mgL-1). The same phenolic composition was observed within the rest of the products where capsules have the higher amount of phenolic acids, followed by powders, dried berries and teas (eg. p-coumaric 81.36; 79.76; 36.28; 28.81 mg/100 g dry matter, respectively). According to flavonol amount, all observed products had higher values of quercetin compared to kaempferol. Obtained results represents a valuable set of data for novel and under-examined plant source of health promoting bioactivecompounds.